Capacity assessment of the creation and development of regional brands in Guilan province - Faghih Abdollahi, Atefeh; Soltani, Ali; Zali, Nader (TeMA - Journal of Land Use, Mobility and Environment, 2025)
<span class="NormalTextRun SCXW241108386 BCX0" data-ccp-parastyle="Abstract" data-ccp-parastyle-defn=""ObjectId":"fe0017e7-5150-5d7c-ac64-5f509ec11579|1","ClassId":1073872969,"Properties":[201342446,"1",201342447,"5",201342448,"1",201342449,"1",469777841,"Tahoma",469777842,"Tahoma",469777843,"Calibri",469777844,"Tahoma",201341986,"1",469769226,"Tahoma",268442635,"18",469775450,"Abstract",201340122,"2",134234082,"true",134233614,"true",469778129,"Abstract",335572020,"1",335551547,"1033",335559740,"276",201341983,"0",335559739,"0",335551550,"6",335551620,"6",469778324,"Normal"]">This study investigates the capacity for regional branding for Guilan province concerning the existing brands’ identification, new brands’ creation opportunities, and development obstacles. The current mixed-method study by using MICMAC analysis method describes the main variables affecting branding results. Its findings recognize tourism, agriculture, and horticulture as the most dominant existing brands and ecotourism, agritourism, and commercial tourism as having huge development potential. Inferior infrastructure, inadequate coordination among stakeholders, and lack of governmental support are major barriers. The study proposes practical solutions to overcome these barriers and to use regional assets effectively. The findings present critical views for policymakers and stakeholders toward the competitiveness and sustainable development of Guilan.